Geraniol as a Potential Stimulant for Improving Anthocyanin Accumulation in Grape Berry Skin through ABA Membrane Transport - Norika Mikami; Mayu Konya; Shinichi Enoki; Shunji Suzuki (Plants, 2022)
Climate change, particularly warmer temperature, has resulted in reduced anthocyanin accumulation in grape berry skin. Because anthocyanin is a crucial determinant of red wine quality, viticulturists need to devise a solution for mitigating the poor coloration of red/black grape berry skin under elevated temperature conditions. In this study, we investigated the effects of geraniol on anthocyanin accumulation in grape berry skins of field-grown grapevines and elucidated the molecular mechanisms of the geraniol-triggered anthocyanin accumulation. Geraniol-treated bunches showed enhanced anthocyanin accumulation in berry skins at harvest (50 days after treatment). Geraniol treatment upregulated the transcription of MybA1 and UFGT, which encode the key factors in anthocyanin biosynthesis, in berry skins. Geraniol treatment also improved anthocyanin accumulation in grape cultured cells. We isolated grape ATP-binding cassette transporter G family protein VvABCG40, encoding abscisic acid (ABA) membrane transporter, from geraniol-treated grape cultured cells. VvABCG40 transcription was upregulated in berry skins 40 days after treatment. Geraniol treatment also upregulated the transcription of VvPP2C24, which encodes ABA-responsible type 2C protein phosphatases, in berry skins, but not the transcription of VvNCED1, which encodes a key enzyme in ABA biosynthesis. Taken together, geraniol-triggered anthocyanin accumulation in berry skins is promoted by ABA membrane transport and not by ABA biosynthesis, and geraniol treatment of field-grown grape bunches may contribute to alleviating the poor coloration of berry skin as a novel technique in viticulture.